The proteomes of transcription factories containing RNA polymerases I, II or III. - Melnik, S; Deng, B; Papantonis, A; Baboo, S; Carr, I; Cook, P (2011)
Human nuclei contain three RNA polymerases (I, II and III) that transcribe different groups of genes; the active forms of all three are difficult to isolate because they are bound to the substructure. Here we describe a purification approach for isolating active RNA polymerase complexes from mammalian cells. After isolation, we analyzed their protein content by mass spectrometry. Each complex represents part of the core of a transcription factory. For example, the RNA polymerase II complex contains subunits unique to RNA polymerase II plus various transcription factors but shares a number of ribonucleoproteins with the other polymerase complexes; it is also rich in polymerase II transcripts. We also describe a native chromosome conformation capture method to confirm that the complexes remain attached to the same pairs of DNA templates found in vivo.